In vitro Antioxidant and Anti-obesity Activities of Freeze-dried Canarium sp., Averrhoa bilimbi L. and Malus domestica - Sri Utami; Susi Endrini; Said Nafik; Intan Meila Tria Lestari; Dea Anindya; Engkay Abu Bakar; Fahrul Rozy; Fathonah Fatimatuzahra Said; Ervi Afifah; Seila Arumwardana; Hayatun Nufus; Dwi Davidson Rihibiha; Hanna Sari Widya Kusuma; Satrio Haryo Benowo Wibowo; Wahyu Widowati (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: The number of obesity cases is still increasing worldwide and has reached an epidemic scale. Plants are known to have a protection role in the development of obesity, however their antioxidant and anti-obesity activities have not widely known. This study was conducted to assess the in vitro antioxidant and anti-obesity activities of different types of freeze-dried fruits cultivated in Indonesia, especially Canarium sp., Averrhoa bilimbi L. and Malus domestica.METHODS: Total phenolic content of freeze-dried fruits was identified by Folin-Ciocalteu method, while the total flavonoid content was measured by aluminium chloride colorimetric assay. To assessed the antioxidant activity, 2,2-diphenyl 1-picrylhydrazyl (DPPH) scavenging activity assay and 2,2’-azino-bis (3-ethylbenzothiazoline6-sulphonic acid) (ABTS) reducing activity assay were performed. The α-amylase and lipase inhibitory activity assay were performed to assess the anti-obesity activity. For comparison, hydroxycitric acid (HCA) compound was also assessed with DPPH, ABTS, α-amylase and lipase assays.RESULTS: A. bilimbi had the highest total phenol content (6.35 µg GAE/mg), meanwhile M. domestica had the highest total flavonoid content (2.06 µg QE/mg). A. bilimbi also showed the highest antioxidant activity both in DPPH and ABTS assay, with inhibitory concentration (IC50)=279.99 µg/mL and 631.78 µg/mL, respectively. The freeze-dried M. domestica had the highest anti-α-amylase activity (IC50=258.85 µg/mL), while Canarium sp. had the highest anti-lipase activity (IC50=118.66 µg/mL).CONCLUSION: Freeze-dried fruits demonstrate in vitro benefits toward obesity. A. bilimbi has potent antioxidant activity and is beneficial against obesity-related adverse health effect by relieving oxidative stress. M. domestica and Canarium sp. hamper the fat accumulation by reducing the carbohydrate absorption and dietary lipid.KEYWORDS: antioxidant, anti-obesity, Canarium sp., Averrhoa bilimbi L., Malus domestica, hydroxycitric acid